Photometric Investigations of Peculiar spiral galaxy NGC 2608 Using Multiband CCD Camera - Ali , Sinan H.; Shafeq, Mohammed S. (Iraqi Journal of Science, 2022)
The structural of peculiar spiral galaxy NGC 2608 have been studied using multiband CCD surface photometry of the observations that have been obtained by the 1.88 m optical telescope of Kottamia Astronomical Observatory (Egypt). We studied the structure and radial brightness distribution of the galaxy. The surface brightness distribution indicate that the center of the galaxy consist of two nucleus. The photometric parameters of its components and the color distribution over the galactic are estimated and stellar populations in different regions of the galaxy are analyzed using color diagram. The distributions of the color indices show that the observed photometric symmetry in the inner part of the galaxy, including the bar, is due to a symmetric distribution of absorbing material. The bluest regions of star formation are located in Eastern side of the bar. From the observations, the surface brightness, Ellipticity of the isophotes, Major axes position angle and color indices are discussed.